1996
DOI: 10.1111/j.1476-5381.1996.tb15991.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cardiac chloride conductance by the tyrosine kinase inhibitor, genistein

Abstract: 1 Genistein (GST), an inhibitor of protein tyrosine kinase (PTK), Na3VO4 (VO4), an inhibitor of phosphotyrosine phosphatase (PTPase), and forskolin (FSK), an activator of the cyclic AMP-dependent, cystic fibrosis transmembrane conductance regulator (CFTR) Cl-channel, were applied to guinea-pig ventricular myocytes to probe for a possible role of tyrosine phosphorylation in the regulation of cardiac Cl-channels. 2 Myocytes in the standard whole-cell configuration were pulsed to various potentials and Cl-current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 48 publications
(63 reference statements)
3
32
3
Order By: Relevance
“…The genistein-induced shifts were almost certainly due to activation of outwardly rectifying I Cl(CFTR) as previously reported (Shuba et al, 1996;Chiang et al, 1997;Shuba & McDonald, 1997), whereas the A23-induced shifts were unrelated to Cl À pathways because they were unaffected by changes in dialysate Cl À concentration. A further distinction between genistein-and A23-induced current was that A23-induced current was strongly inhibited by Cd 2 þ .…”
Section: Properties Of the Current Induced By A23supporting
confidence: 68%
See 1 more Smart Citation
“…The genistein-induced shifts were almost certainly due to activation of outwardly rectifying I Cl(CFTR) as previously reported (Shuba et al, 1996;Chiang et al, 1997;Shuba & McDonald, 1997), whereas the A23-induced shifts were unrelated to Cl À pathways because they were unaffected by changes in dialysate Cl À concentration. A further distinction between genistein-and A23-induced current was that A23-induced current was strongly inhibited by Cd 2 þ .…”
Section: Properties Of the Current Induced By A23supporting
confidence: 68%
“…Verapamil (SigmaAldrich) was dissolved in water and diluted in the bathing solution. Aqueous stock solutions (100 mM) of Na 3 VO 4 (orthovanadate) (Fisher Scientific, Nepeon, ON, Canada) were freshly prepared, and the pH was adjusted to B10 (Gordon, 1991;Shuba et al, 1996). Appropriate amounts of stock solution were added to the superfusate just before use, and the pH was readjusted to 7.4 with NaOH.…”
Section: Drugsmentioning
confidence: 99%
“…Genistein (GST) is a selective inhibitor of tyrosine kinase (TK) [2,20] that has been reported to activate cyclic adenosine monophosphate (cAMP)-dependent cystic fibrosis transmembrane conductance regulator (CFTR) Cl -channels in a variety of cells [26,32,40,52], including guinea-pig ventricular myocytes [7,8,41,43]. Some investigators have suggested that GST "directly" activates CFTR [8,12,52], whereas others have concluded that GST opens CFTR by directly or indirectly inhibiting a phosphatase that dephosphorylates and inactivates the channel [27,38,56].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, GEN was shown to be either pro-apoptotic or anti-apoptotic depending both on its concentration and the cell system [14,[22][23][24]. Similarly, the GEN analogue daidzein (DZN), which does not inhibit TK [25], can inhibit D-gal-induced apoptosis via the Bcl-2/Bax apoptotic pathway [26] and may be a potential medical candidate for neurodegeneration therapy. DZN exhibits an antioxidant activity [27] and shows other biological properties, including estrogen-like and estrogenin-dependent effects [for refs see 28].…”
mentioning
confidence: 99%